O Smartphone Global: Uma tecnologia para além dos jovens; The Global Smartphone - Miller, Daniel; Abed Rabho, Laila; Awondo, Patrick; de Vries, Maya; Duque, Marília; Garvey, Pauline; Haapio-Kirk, Laura; Hawkins, Charlotte; Otaegui, Alfonso; Walton, Shireen; Wang, Xinyuan (UCL Press, 2022)
undefined